Analysis of clinical characteristics and predictive model for effective treatment of tinnitus in patients with transient compound sound therapy - Yuan, Hao; Ma, Peng-Wei; Chen, Jia-Wei; Wang, Wei-Long; Gao, Wei; Lu, Pei-Heng; Ding, Xue-Rui; Lun, Yu-Qiang; Wang, Zi; Lu, Lian-Jun (Frontiers in Neurology, 2024)
PurposeThis study explored the clinical characteristics of patients with tinnitus who responded to sound therapy and established a predictive model to evaluate the effectiveness of this therapy according to the clinical characteristics.MethodsA retrospective analysis was performed on 991 subjective tinnitus patients who received compound sound therapy in the Department of Otolaryngology of the local hospital from November 2019 to January 2022.ResultsWe found that tinnitus patients with different therapeutic effects had significant differences in the tinnitus side (p = 0.007), tone loudness distortion feedback test (FBT) (p = 0.000), residual inhibition test (RIT) (p = 0.000), tinnitus frequency (p = 0.012) and sensation level (p = 0.023). The corresponding variables were screened by univariate logistic regression, and the selected variables were analyzed using multivariate logistic regression. The results showed that FBT (p = 0.003), RIT (p = 0.000) and tinnitus frequency (p = 0.029) were independent risk factors affecting the efficacy of compound sound therapy. A predictive model and nomogram for the efficacy of compound sound therapy for tinnitus were constructed based on independent risk factors. The area under the curve (AUC) of the model constructed in this study was 0.766 (95% CI = 0.725–0.807), indicating a certain prediction ability. The calibration curve revealed that the predicted results were in good agreement with the actual results.ConclusionThe model can predict the prognosis of tinnitus in patients receiving compound sound therapy and help otolaryngologists make the best clinical decisions regarding tinnitus treatment.